Testing, numerical simulation and design of prestressed high strength steel arched trusses. (15th March 2019) - Afshan, S.; Theofanous, M.; Wang, J.; Gkantou, M.; Gardner, L.
Highlights: Investigation of the structural behaviour of prestressed high strength steel arched trusses. Testing of four prestressed arched trusses fabricated from S460 hot finished square hollow section members. Finite element modelling of prestressed arched truss systems and validation of models against the conducted tests. Parametric studies examining the effect of prestress level, material grade and the top chord cross-section. Development of design recommendations for prestressed arched truss systems. Abstract: The structural behaviour of prestressed high strength steel arched trusses is studied in this paper through experimentation and numerical modelling. Four 11 m span prestressed arched trusses fabricated from S460 hot finished square hollow section members were loaded vertically to failure. Three of the tested trusses were prestressed to different levels by means of a 7-wire strand cable housed within the bottom chord, while the fourth truss contained no cable and served as a control specimen. Each truss was loaded at five points coinciding with joint locations along its span, and the recorded load-deformation responses at each loading point are presented. Inclusion and prestressing of the cable was shown to delay yielding of the bottom chord and enhance the load carrying capacity of the trusses, which ultimately failed by either in-plane or out-of-plane buckling of the top chord. For the tested trusses, around 40% increases in structural resistance were achieved through the addition of the cable, though the self-weight was increased by only approximately 3%. In parallel with the experimental programme, a finite element model was developed and validated against the test results. Upon successful replication of the experimentally observed structural response of the trusses, parametric studies were conducted to investigate the effect of key parameters such as prestress level, material grade and the top chord cross-section on the overall structural response. Based on both the experimental and numerical results, design recommendations in the form of simple design checks to be performed for such systems are provided.